Penerapan Green Economy dalam Upaya Peningkatan Ekonomi Masyarakat melalui Pemanfaatan Lahan Kosong Pekarangan Rumah: Studi Literatur Riview - Nasruddin Nasruddin; Madnasir Madnasir; Muhammad Iqbal Fasa; Firqotus Sa'idah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The environment is the main thing that needs to be preserved by humans, the problems that often occur in this country are not spared from environmental problems. So that this problem is not only the individual responsibility of a State but also the responsibility of all human beings in the world. This article aims to describe the concept of a green economy in an effort to increase community income through the use of yard land that plays a role in environmental conservation in the form of coolness, harmony, beauty, and even helping to mitigate greenhouse gases. The research was conducted qualitatively using literature analysis tools or review of review.  Literature review studies are a method used by researchers to collect data or find out sources related to this topic that can be obtained from various sources such as journals, books, the internet, and other sources. The data was obtained by searching for literature sources.  The result in this study is that the green economy is an economic behavioral concept that pays attention to economic growth along with the concept of preventing damage to the natural environment and declining environmental quality. Which results in an increase in human well-being and social well-being.  One of them is the use of yard land which currently focuses on vegetable cultivation businesses that can meet family needs and be sold to increase family income.  By preserving theenvironment the family's income increases, human welfare and social welfare will be fulfilled.